Epistemology of Tafsir Anfās al-Maḥāsin fī Tafsīr Sūrat Yāsīn by K.H. Syaikhul Islam Ali Masyhuri - Muhammad Muslich Aljabbar (KURAS Institute, 2025)
In January 2025, a new tafsir work entitled Anfās al-Maḥāsin fī Tafsīr Sūrat Yāsīn from Sidoarjo, authored by K.H. Syaikhul Islam Ali Masyhuri, a prominent scholar from the Progressive Islamic Boarding School Bumi Shalawat. This work remains largely unexplored in academic discourse, and its aesthetically chosen title reflects the author’s distinctive approach to interpreting Sūrat Yāsīn. This study aims to examine the epistemology of Anfās al-Maḥāsin, with focus on its interpretive methodology and the validity of its exegesis. Using a qualitative method based on library research, data were gathered from the primary text and relevant secondary sources. The analysis applies the perspective of Saifuddin Herlambang to evaluate the methodology and Abdul Mustaqim to assess the validity. The results show that K.H. Syaikhul combines the bi al-riwāyah approach by referring to the Al-Qur’ān, Prophetic traditions, views of the companions, Tābiʿīn, and mufasir, with bi al-dirāyah rooted in ijtihād, but grounded in authoritative references. He employs the tafsīr ijmālī method in mushafic sequence, with a maqāṣidī pattern. Although it has limited scientific correspondence, its coherence remains strong. This tafsir is relevant to the needs of people today. This study offers a foundational step for future academic research on this tafsir.